Norberto Bobbio: from the international system to the theory of war and peace - Carinheno, Gabrielle Custódio (2019)
This article aims to analyze the theories of war and war/peace in the international thinking of the Italian philosopher Norberto Bobbio, and to present the importance of building a democratic state for this theme. The article is fundamental to explore more in-depth materials little analyzed about the international system in Bobbian thought, although internally, his texts are extremely studied. In this way, there is a great importance due to the greater academic emphasis granted to the themes of democracy and peace-war than to its international thinking, consubstantiating an intellectual gap in the studies on the thought of this important contemporary thinker.